Prognostic Factors in Acute Methadone Toxicity: A 5-Year Study - Abbas Aghabiklooei; Maryam Edalatparvar; Nasim Zamani; Babak Mostafazadeh (Journal of Toxicology)
Background. Delayed or recurrent profound respiratory depression, ventricular dysrhythmias, acute lung injury, and death are the major complications of MTD overdose. We aimed to clarify the prognostic factors in MTD toxicity. Materials and Methods. Retrospectively, medical files of all patients poisoned by MTD and older than 12 years of age who had presented to Loghman Hakim Poison Center between 2007 and 2012 were evaluated. The data was compared between survivors and nonsurvivors. Results. Twenty-eight out of 322 patients died (mortality rate = 8.7%). MTD-related death was higher in patients with acute on chronic toxicity who were on daily dose of MTD and had ingested higher doses (in comparison to those with acute toxicity due to first-time exposure; 13% versus 6%). Renal failure was the most common medical complication related to deaths due to MTD toxicity. Conclusions. Based on previous researches, the most common cause of MTD overdose-related deaths is respiratory impairment; however, in our study, acute renal failure with or without rhabdomyolysis was the main delayed cause of deaths in MTD-poisoned patients. Antidotal therapy, early recognition, and treatment of hemodynamic compromise and rhabdomyolysis can be life-saving in these patients.